Whether and When Did Bitcoin Sentiment Matter for Investors? Before and During the COVID-19 Pandemic - Aysan, Ahmet Faruk; Mugaloglu, Erhan; Polat, Ali Yavuz; Tekin, Hasan (Springer, 2023)
Using a wavelet coherence approach, this study investigates the relationship between Bitcoin return and Bitcoin-specific sentiment from January 1, 2016 to June 30, 2021, covering the COVID-19 pandemic period. The results reveal that before the pandemic, sentiment positively drove prices, especially for relatively higher frequencies (2-18 weeks). During the pandemic, the relationship was still positive, but interestingly, the lead-lag relationship disappeared. Employing partial wavelet tools, we factor out the number of COVID-19 cases and deaths and the Equity Market Volatility Infectious Disease Tracker index to observe the direct relationship between a change in sentiment and return. Our results robustly reveal that, before the pandemic, sentiment had a positive effect on return. Although positive coherence still existed during the pandemic, the lead-lag relationship disappeared again. Thus, the causal relationship that states that sentiment leads to return can only be integrated into short-term trading strategies (up to six weeks frequency).
Mugaloglu, Erhan/0000-0001-5362-6259; Polat, Ali Yavuz/0000-0001-5647-5310; Tekin, Hasan/0000-0003-2855-215X; Aysan, Ahmet Faruk/0000-0001-7363-0116
Keywords: Bitcoin; Return; COVID-19; Sentiment; TRMI; C21; C22; G11; G14; G17